The Influence of Organizational Culture and Work Environment on Employee Loyalty - Widuri, Verissa Berliana; Widjanarko, Gita Pratiwi; Batu, Kardison Lumban (Economic and Business Horizon, 2025)
Employees are one of the most important assets for a company; therefore, it is essential for companies to build employee loyalty. This is because employees with high levels of loyalty contribute significantly to the achievement of organizational goals. This study aims to analyze the influence of organizational culture and work environment on employee loyalty. The research employed a quantitative method with an explanatory approach. The population of this study consists of Gen Z employees across various industries, with purposive sampling as the sampling technique. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 25.0. The results indicate that organizational culture has a positive influence on employee loyalty. Similarly, the work environment also has a positive impact on employee loyalty. Simultaneously, organizational culture and work environment have a positive and significant influence on employee loyalty. These findings emphasize the importance of a strong organizational culture and a conducive work environment in fostering long-term employee commitment to the company. Based on the results, it is recommended that companies consistently strengthen organizational cultural values and create a work environment that supports employee well-being and productivity in order to enhance loyalty.